Detection of Partial Central Diabetes Insipidus in Limited Resource Setting - Merci M. Pasaribu; Dina Nurul Istiqomah; Dewi Wulandari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Antidiuretic hormone (ADH) is an endogenous prohormone peptide synthesized in the posterior hypothalamus that regulates water excretion by the kidney. Diabetes insipidus is a disorder characterized by the excretion of large amounts of urine (diabetes) that are hypotonic, watery, and tasteless (insipid). The rarity of this case is one of the causes of missed diagnosis. If not diagnosed properly, patients will receive therapy that exacerbates the disease. The Water Deprivation Test (WDT) is one of the dynamic tests that can be done to narrow the diagnosis. A 44-year-old female was admitted to the hospital with chief complaints of polydipsia and polyuria during the previous 9 months. The patient had a history of irregular menstruation, cesarean delivery due to abdominal mass, and breast lump surgery. Diabetes mellitus and thyroid disease were excluded. Her blood pressure during admission was 150/100 mmHg and her body mass index was 31.1. Fluid balance data obtained before the water deprivation test showed that the urine volume (output) was 7.150 mL per 24 hours, and the total water input was 6.290 mL. Water deprivation test results showed that the kidneys were partially respond to the administration of exogenous ADH, suggestive of partial central diabetes insipidus.